Analisis Program Sekolah Mengaji di SDN Panggilingan 01 Bandung - Teriana Nopianti; Enoh; Dewi Mulyani (Bandung Conference Series: Islamic Education, 2022)
Abstract. Considering that currently in general school-age children, especially at SDN Calling 01, which is more precisely grade 5, have not been able to read the Qur'an well, while reciting the Koran is very important and useful for people who study it, so as not to lose the child's love -children to the Qur'an and keep inflaming the holy verses of the Qur'an. This study aims to: 1.) Find out how the planning of the Koran school activity program is implemented at SDN Callingan 01 2.) the process of implementing the Koran program at SDN Callingan 01 3.) Knowing the supporting and inhibiting factors in implementing the Koranic school program at SDN Callingan 01. Based on the results of the analysis, it is shown that before implementing the school program, the school and the teacher of the Koran held a maximum learning plan. So from the results that the researchers got, regarding the study program at SDN Callingan 01 the learning indicators were able to be followed by students well so that learning scores could be achieved and categorized as complete. Abstrak. Mengingat saat ini pada umumnya anak-anak usia Sekolah terutama di SDN Panggilingan 01 yang lebih tepatnya kelas 5 belum mampu untuk membaca Al- Qur’an dengan baik, sedangkan mengaji itu sangat penting dan bermanfaat bagi orang yang mempelajarinya, agar tidak hilangnya rasa cinta anak-anak terhadap Al-Qur’an dan tetap menggelorakan ayat-ayat suci Al-Qur’an. Penelitian ini yang bertujuan untuk :1.) Mengetahui bagaimana perecanaan program kegiatan Sekolah mengaji yang diterapkan di SDN Panggilingan 01 2.) proses pelaksanaan program mengaji di SDN Panggilingan 01 3.) Mengetahui faktor pendukung dan penghambat dalam melaksanakan program Sekolah mengaji di SDN Panggilingan 01. Berdasarkan hasil analisis menunjukkan bahwa sebelum melaksanakan program Sekolah mengaji pihak Sekolah dan guru mengaji mengadakan perencanaan pembelajaran yang maksimal. Maka dari hasil yang peneliti dapat, mengenai program Sekolah mengaji di SDN Panggilingan 01 indikator pembelajaran mampu diikuti siswa-siswi dengan baik sehingga dapat tercapainya nilai pembelajaran dan dikategorikan tuntas.